2008
DOI: 10.3170/2008-8-18377
|View full text |Cite
|
Sign up to set email alerts
|

Flood pulsing and metacommunity dynamics in a desert riparian ecosystem

Abstract: Questions: 1. Does flood pulsing drive metacommunity dynamics and provide insurance against catastrophic flooding in desert southwestern riparian ecosystems? 2. Do upland and wetland species in the floodplain differ in their dynamics? Location: Southwestern USA. Methods: We sampled vegetation and propagule banks in four communities along a floodplain hydrogradient. Plant species were classified as wetland or upland and community wetland indicator scores were calculated. ANOVA tested for differences between dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…This linkage across lateral gradients contributes to high diversity within a riparian site (Boudell and Stromberg 2008b). This study, by showing high similarity in composition of seed banks between hydrologic site types along the river continuum, and by showing increased similarity of extant plant communities between site types during wetter conditions, suggests that the metacommunity concept may apply along the longitudinal river dimension as well.…”
Section: Implications For Conservationmentioning
confidence: 73%
See 1 more Smart Citation
“…This linkage across lateral gradients contributes to high diversity within a riparian site (Boudell and Stromberg 2008b). This study, by showing high similarity in composition of seed banks between hydrologic site types along the river continuum, and by showing increased similarity of extant plant communities between site types during wetter conditions, suggests that the metacommunity concept may apply along the longitudinal river dimension as well.…”
Section: Implications For Conservationmentioning
confidence: 73%
“…This indicates that propagules of wetland plants are widely distributed among the various reach types of spatially intermittent rivers. This distribution may develop because Xood Xows broadly disperse seeds within river corridors, homogenizing species pools (Johansson et al 1996;Goodson et al 2003;Jansson et al 2005;Boudell and Stromberg 2008b), or because of episodic in situ seed production during very wet conditions. Precipitation and stream Xow are highly variable through time in desert environments, and the diVering meteorological and hydrological conditions trigger germination of diVerent assemblages of species from soil seed banks (Nicol et al 2003;Robertson and James 2007;Capon 2007).…”
Section: Species Richnessmentioning
confidence: 99%
“…Their apparent affinity at the scale of the whole patch is probably caused by their co-occurrence in particular patches where local conditions are more suitable, possibly related to water availability. Flood pulsing is a mechanism that structures and connects riparian plant communities via flood dispersal (Naiman et al 1993;Middleton 2000) and drives metacommunity dynamics in deserts (Boudell and Stromberg 2008). It has been shown that flood pulsing disperses propagules into a variety of microenvironments, many with inappropriate moisture conditions, and that some seed species may escape local extinction by persisting in the propagules bank until flood pulsing creates moisture conditions that are more suitable (Leck and Brock 2000;Boudell and Stromberg 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that flood pulsing disperses propagules into a variety of microenvironments, many with inappropriate moisture conditions, and that some seed species may escape local extinction by persisting in the propagules bank until flood pulsing creates moisture conditions that are more suitable (Leck and Brock 2000;Boudell and Stromberg 2008). Although blue fan palm seed dispersal by vertebrates is significant in these oases (Wehncke et al 2009), large-scale flood pulsing might produce important homogenization of floodplain propagules banks (Boudell and Stromberg 2008). Seed species may thus be transported across the floodplain into a variety of microsites and species arrayed along some environmental gradient (such as water gradients in riparian ecosystems, Naiman et al 2005), according to their life-history traits and strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation